The "war on drugs" has failed: is decriminalization of drug use a solution to the problem in South Africa? - Fellingham, Robyn (My University, 2013)
This research report will engage in the debate surrounding decriminalization of drug use and whether it is a possible solution to the problem of drug use in South Africa. This is a question becoming more prevalent in global discussions regarding drug policy and its efficacy. It is held in the report that when evaluating policy two aspects must be addressed; namely the philosophical justification for the policy and the efficacy of the policy. Regarding criminalization it is found that policy may be justified by the public harm principle but that it does not effectively achieve the purpose of preventing and decreasing drug use and associated burdens. Thus, it is argued that prohibition is a constitutional limitation, but does not necessarily achieve its purpose in the least repressive or most effective way. Finally it is suggested that the solution to the drug problem will be one which addresses the background, particularly socio-economic, to drug use. Decriminalization has the theoretical potential to address this context but further empirical research is required in order to establish evidential grounds for continued discussion.
Keywords: Substance Abuse; Drugs